Partial differential equations and boundary value problems with maple - Articolo, George A. (Elsevier, 2009)
Partial Differential Equations and Boundary Value Problems with Maple presents all of the material normally covered in a standard course on partial differential equations, while focusing on the natural union between this material and the powerful computational software, Maple.